Miniplate Removal Post-Open Reduction Internal Fixation: A Retrospective Analysis - ALBERT, DYNA; MUTHUSEKHAR, M R; SELVARASU, KATHIRAVAN (The journal of contemporary issues in business and government, 2021)
Evolution of fracture management after the advent of asepsis and anesthesia has changed its trend toward open reduction and internal fixation(ORIF). In maxillofacial skeleton, to re-establish both form and function, semi-rigid fixation has been favored in recent times. Miniplates are commonly made of stainless steel and titanium. The fate of these post-ORIF is still controversial with both schools of thought providing substantial valid arguments. Aim of this study is to assess the incidence, site, type of material and reason for miniplate removal. This retrospective observational study was conducted among patients who reported to the Department of Oral and maxillofacial surgery, Saveetha Dental College, Chennai between June 2019 to March 2020. Inclusion criterias were patients of both gender and any age group undergoing miniplate removal post-ORIF and exclusion criteria were those undergoing hardware removal secondary to other procedures like orthognathic or reconstructive surgery and patients who are suffering from debilitating injuries physically and mentally challenged patients. Among 17 patients evaluated, incidence of miniplate removal was more common in males (76.5%) in the third decade of life. Infection (82.4%) was the most common reason for removal, while stainless steel was the most common type of miniplate removed (82.4%). 88.2% of miniplates removed had an adjacent dentate structure. No association was found between reason for removal and type of miniplate, proximity to dentate structure and reason for removal. Prospective studies and systematic analysis required to arrive at consensus.